STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PADA “KEDAI ANEKA JUS” GRESIK (Jurnal Bisnis Indonesia, 2022)
The development of the era can affect the development of technology. With the development of this technology, it affects the marketing industry in Indonesia. The emergence of relatively small companies and relatively large companies. In this way, the marketing mix strategy will increase in increasing sales volume at Kedai Aneka Jus Gresik. The marketing mix strategy has the concept of marketing success to support the resulting product. And with this marketing mix, Kedai Aneka Jus optimizes services, and makes various product innovations and flavors that are always consistent and at affordable prices that can attract consumers' interest. And take advantage of opportunities to increase sales. In this study, the researcher used a qualitative type of research. In this qualitative research, it is carried out by field research and can also be considered a broad approach as a method for collecting qualitative data. This type of qualitative research is used to examine the sample and research population, the sampling technique is generally done by purposive sampling, while the data collection is usually done by in-depth interview sampling technique. The informants in this study were (1) the owner of the Assorted Juice Shop, and (2) the Consumers of the Assorted Juice Shop. DOI : https://doi.org/10.33005/jbi.v13i1.3074